An Assessment of Social Media Usage Patterns and Social Capital: Empirical Evidence From the Agricultural Systems of China - Xie, Gui-hua; Wang, Lin-ping; Khan, Asif (Frontiers in Psychology, 2021)
This research study provides a theoretical model to measure the impact of social media usage on social capital in the agricultural system of China. Furthermore, this research also investigates the correlation between agricultural policies related to entrepreneurship training and social media usage. A total of 589 questionnaire surveys were distributed in the training courses of Fujian Agricultural Vocational Technology College, and, Fuzhou, Quanzhou, Jianning, and Liancheng counties and cities in Fujian during winter and summer vacations to target new vocational farmers. The results show that social use, hedonic use, and cognitive use of social media significantly impacted both bridging and bonding social capital. Furthermore, the results of the study suggest that entrepreneurs who have participated in the training have significantly higher levels of social use and cognitive use than those who have not been trained. The findings of this paper have implications for the digital transformation by agricultural entrepreneurs in recognition of the role of sustainable education and learning in entrepreneurial activities and the utilization of social and cognitive functions of social media to acquire and accumulate social capital and provide support for sustainable agriculture and rural development. Furthermore, the concepts of sustainability-driven agriculture in the digital transformational framework were also studied and it was indicated that transformed agriculture can effectively deal with the present challenges.